An Analysis of the Psychological Stressors among Hearing Impaired Children with Conversion Disorder - Hifsa Batool,; Adila Khanam, (JIE, 2025)
The signs and symptoms of conversion disorders emerge due to the reaction of any psychological stressful event in one's life. The purpose of this study was to analyze the psychological stressors in hearing impaired children with conversion disorder and to evaluate the occurrence of various stressors based on their demographic characteristics. This was a descriptive study, and a questionnaire was used through survey method to collect the data. Population of the study was all the children receiving their treatment of conversion disorder from different hospitals of Punjab province, Pakistan. Sample of the study was 40 hearing impaired children with conversion disorder selected through purposive sampling technique. All the participants of the study were firstly assessed according to the criteria of conversion disorder described in (Diagnostic and Statistical Manual of Mental Disorders-V) DSM-V. Life events scale was administered to collect data for psychological stressors that the hearingimpaired students were facing currently and that trigger them towards this ailment. Statistical analysis demonstrated that gender, residential area, number of siblings and birth order effect the lives of the hearing-impaired children with conversion disorder as girls with conversion disorder experience high level of psychological stress as compared to the boys with conversion disorder. Meanwhile rural children, only child and the children who were from younger age group experience high level of psychological stress. It can be concluded from the findings of this study that government and non-government organization should arrange workshops and seminar for the counseling of parents and to teach them how to deal with their hearing-impaired children when they demand excessively and to teach the parents about their responsibilities in the development of their hearingimpaired children.